Transfictional Character and Transmedia Storyworlds in the British Nineteenth Century - Haugtvedt, Erica (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Transfictional Character and Transmedia Storyworlds in the British Nineteenth Century is an exciting and long-overdue application of fan studies to the 19th century literary world. Haugtvedt shows how the mass storytelling culture developed by the early Victorians resulted in the transmedia extensions of popular novels via penny press plagiarisms, printed illustrations, retellings in song, tie-in marketing and costuming, and cheap theatrical adaptations, and argues that these practices anticipate and are usefully compared to fandom practices of the 20th and 21st centuries. This book bridges an important gap in the field between more overtly folk practices and modern media fandom: for once, Sherlock Holmes is the end, not the start, of the story." -Francesca Coppa, Ph.D., Muhlenberg College, USA. This book is a study of how transfictional and transmedia storytelling emerges in the nineteenth century and how the period's receptive practices anticipate the receptive practices of fandom and transmedia storytelling franchises in the twentieth and twenty-first centuries. The central claim is that the serialized, periodical, and dramatic media environment of the late eighteenth century through the nineteenth century in Great Britain trained audiences to perceive the continuous identity of characters and worlds across disparate texts, illustrations, plays, and songs by creators other than the earliest originating author. The book contributes to fan studies, transmedia studies, and nineteenth-century periodical studies while also interrogating the nature of fictional character. Erica Haugtvedt is Assistant Professor of English in the Humanities Department at South Dakota Mines in Rapid City, South Dakota, USA. She specializes in nineteenth-century British literature, media and advertising history, and popular culture. She received her PhD in English from Ohio State University in 2015. She works on the serial Victorian novel and its contemporaneous adaptations-particularly focusing on serial character across media. Her articles have appeared in Victorian Studies, Victorian Periodicals Review, Transformative Works and Cultures, and Victorian Popular Fictions Journal.
1. Introduction: From Novel Studies to Fan Studies -- 2. Pickwick Abroad (1837-1838): Transfictional Character as Permanent Object -- 3. Jack Sh Sheppard (1839-1840): Class and Complex Transfictional Character -- 4. Trilby (1894) in the Marketplace: fin de siècle Merchandising and Transfictional Character as Branded Object -- 5. Sherlock Holmes (1887-1930) and Believing in Character -- 6. Afterword.
Keywords: Ethnology-Great Britain; Culture; Literature, Modern-19th century; Audiences; British Culture; Nineteenth-Century Literature; Fan and Audience Studies